Soviet Union: to the centenary of formation - A. N. Kostyukov (Правоприменение, 2022)
The subject. The article analyzes the constitutional and legal aspects of the formation of the USSR in the context of the theory of federalism. In the course of this analysis, the author examines the constitutional norms regulating the status of sovereign republics as members of the federation.The purpose of the paper is to classify USSR as a type of federation according to its constitutional regulation during all its existence as a state, and to define legal causes of falling soviet federalism experience.The methodology of the study includes general scientific methods (analysis, synthesis, description) and legal methods. In addition to this, historical method was also applicable.The main results and scope of their application. Taking into account various theoretical approaches to the classification of federations, the author comes to the conclusion that the USSR was formally created as a constitutional federation, since the issues of state sovereignty, the right to withdraw from the union and the competence of the new state were fully defined precisely in the Constitution of the USSR of 1924. At the same time, the functioning of public authority in the USSR on a contractual, consensual basis of central and regional authorities was absent.Conclusions. The Soviet Union came to the end of its existence almost in the status of a confederation, having in its composition sovereign states with independent legal systems, state sovereignties and established international relations for some of them.A lot of constitutional risks were laid in the previous periods of development of federal relations in the USSR and their consolidation at the constitutional level strengthened the centrifugal forces and brought eventually to be adopted on June 12, 1990 the Declaration on State Sovereignty of the RSFSR.